2020
DOI: 10.1002/rth2.12333
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of thrombotic events in cold agglutinin disease: A 10‐year retrospective analysis

Abstract: Background Cold agglutinin disease (CAD) is a rare autoimmune hemolytic anemia mediated by IgM autoantibodies that trigger hemolysis via classical complement pathway. Increased incidence of thrombotic events (TEs) has been reported in patients with other forms of hemolysis. The incidence of TEs in patients with CAD is unknown. Objective Evaluate TE risk in patients with CAD. Patients/Methods This is a matched cohort comparison study evaluating the risk of TEs in patients with CAD and without CAD over a 10‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 21 publications
0
64
2
Order By: Relevance
“…Multiple studies have seen an association between cold agglutinin disease and thrombotic events. 8 Chapin et al discussed the increased risk of thrombotic events in those with cold agglutinin disease. 9 Bleakly et al showed a relationship between DIC and cold agglutinin hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have seen an association between cold agglutinin disease and thrombotic events. 8 Chapin et al discussed the increased risk of thrombotic events in those with cold agglutinin disease. 9 Bleakly et al showed a relationship between DIC and cold agglutinin hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…AIHA is a group of rare (1–3 cases per 100,000 person-years) [ 3 ] and heterogeneous diseases characterized by the presence of autoantibodies that react against red blood cell self-antigens and could lead to a variety of life-threatening complications including thrombosis. After the first evidence in the 1960’s of the occurrence of pulmonary embolism in 11% of patients with AIHA [ 4 ], a hypercoagulable state has been demonstrated in these patients [ 5 ] and more and more reports have been published making thrombotic manifestations a hallmark of AIHA, as 10–20% of patients experience a thrombotic event, either arterial or venous ( Table 1 ) [ 1 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, one fatal pulmonary embolism has been reported among 21 AIHA patients who received antithrombotic prophylaxis with low-molecular-weight heparin [ 6 ].…”
Section: Incidence and Risk Factors For Venous Or Arterial Thrombosis In Immune Mediated Hemolysismentioning
confidence: 99%
“…Cold agglutinin disease (CAD) is a particular form of AIHA in which the pathogenic autoantibodies are represented by cold agglutinins that trigger hemolysis via classical complement pathway activation. Epidemiological data on thrombotic risk and its impact on mortality rate in patients with CAD are limited, but recently a population-based [ 13 ] and a retrospective cohort study over a 10-year period [ 15 ] reported an approximately two-fold increased risk of thrombotic events compared to non-CAD patients and a shorter follow-up, suggesting a potential increased risk of mortality in patients with thrombotic events. In a phase II study, treatment with eculizumab was associated with the absence of thromboembolic events, although the follow-up period was too short (less than one year) to draw significant conclusions [ 19 ].…”
Section: Incidence and Risk Factors For Venous Or Arterial Thrombosis In Immune Mediated Hemolysismentioning
confidence: 99%
“…Patients can experience acute or chronic hemolytic anemia; hemoglobinuria can be seen with significant complement involvement and intravascular hemolysis. The risk of thrombosis is increased in warm AIHA, particularly during the active phase of the disease [ 17 , 19 ], as well as in cold agglutinin disease [ 20 , 21 ]. In cold agglutinin disease, cold-induced intravascular agglutination results in circulatory symptoms such as acrocyanosis and/or the Raynaud phenomena, which occur in 50–90% of patients [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%